Highly sensitive fluorescence detection technology currently available for HTS. - Eggeling, C; Brand, L; Ullmann, D; Jäger, S (2003)
Homogeneous fluorescence methods are providing an important tool for HTS technologies. A wide range of different techniques have been established on the market, with read-outs ranging from total fluorescence intensity to statistical analysis of fluorescence fluctuations for biochemical assays or fluorescence imaging techniques for cellular systems. Each method has its own advantages and limitations, which have to be accounted for when designing a specific assay. Here, recently developed fluorescence techniques and some of their applications, with a particular focus on sensitivity, are summarized and their principles are presented.